Exogenous Tissue Inhibitor of Metalloproteinase-2 Affects Matrix Metalloproteinase-2 Expression in Conjunctival Filtering Blebs and Bleb Scarring in Rats. (31st May 2018) - Wang, Ling; Liu, Meng-ying; Yin, Gang; Li, Na; Wang, Da-bo
Abstract : Objective . To examine the effect of tissue inhibitor of metalloproteinase-2 (TIMP-2) on conjunctival filtering bleb scarring. Methods . A model of conjunctival filtering bleb was established whereby rats were injected with saline, blank adenoviral vector, or adenoviral vector carrying TIMP-2 into the bleb. Filtration bleb formation and matrix metalloproteinase-2 (MMP-2) expression were examined. Results . All operated eyes formed obvious elevated blebs on day 1. In the normal saline group, empty plasmid group, and gene transfection group maintenance time of filtrating blebs was 5–14, 5–14, and 6–16 days, and average survival time was 8.24, 8.16, and 9.44 days, respectively. MMP-2 expression increased slightly in the gene transfection group at 3 and 5 days after surgery, reached a peak after 14 days, and then gradually decreased. MMP-2 expression was weakly positive in the normal conjunctival epithelium, but was hardly detected in the lamina propria. Seven days after surgery, the epithelium and lamina propria of the conjunctival filtering bleb exhibited strong positive expression in the empty plasmid group but only weak expression in the adenovirus group. Conclusion . Exogenous TIMP-2 interfered with local MMP-2 expression, delaying peak expression of MMP-2 and slowing the scarring of filtering blebs during wound healing of subconjunctival tissue.